The Effectiveness of Interactive Multimedia on Collaboration Skills and Science Learning Outcomes of Fifth-Grade Students at SDN 1 Kalibombong - Merry Metrika; Ristiana Dyah Purwandari (UM Purwokerto Press, 2025)
This mini research aimed to examine the effectiveness of interactive multimedia on collaboration skills and science learning outcomes concerning the human respiratory system among fifth-grade students at SDN 1 Kalibombong. Interactive multimedia on the respiratory system was directly utilized during the learning sessions for fifth graders. This study adopted an experimental research design with a quasi-experimental setup. The research procedure included a preparatory phase with initial observations and the development of research instruments, the implementation phase, and the conclusion phase. The subjects of this study were fifth-grade students at SDN 1 Kalibombong, Banjarnegara district. Data collection techniques used were observations, document analysis, surveys, and tests. Based on the t-test results for the collaboration skills variable, a tvalue of 2.125 was obtained, which is greater than the t-table value of 2.048, thus H1 was accepted. Similarly, the t-test results for the learning outcomes variable showed a tvalue of 3.112, exceeding the t-table value of 2.048, leading to the acceptance of H1. This mini research concludes that interactive multimedia is effective in enhancing collaboration skills and science learning outcomes related to the human respiratory system.